Antibiotic resistance among Helicobacter pylori clinical isolates in Lima, Peru - Boehnke KF; Valdivieso M; Bussalleu A; Sexton R; Thompson KC; Osorio S; Novoa Reyes, I; Crowley JJ; Baker LH; Xi C (Infection and Drug Resistance, 2017)
Kevin F Boehnke,1 Manuel Valdivieso,2 Alejandro Bussalleu,3 Rachael Sexton,4 Kathryn C Thompson,1 Soledad Osorio,5 Italo Novoa Reyes,3 John J Crowley,4 Laurence H Baker,2 Chuanwu Xi1 1Department of Environmental Health Sciences, School of Public Health, 2Division of Hematology Oncology, Department of Internal Medicine, University of Michigan, Ann Arbor, MI, USA; 3Departamento Académico de Clínicas Médicas, Facultad de Medicina Alberto Hurtado, Universidad Peruana Cayetano Heredia, Lima, Perú; 4Cancer Research and Biostatistics, Seattle, WA, USA; 5Dirección General de Salud Ambiental, Ministerio de Salud del Perú, Lima, Perú Objectives: Gastric carcinoma is the most common cancer and cause of cancer mortality in Peru. Helicobacter pylori, a bacterium that colonizes the human stomach, is a Group 1 carcinogen due to its causal relationship to gastric carcinoma. While eradication of H. pylori can help prevent gastric cancer, characterizing regional antibiotic resistance patterns is necessary to determine targeted treatment for each region. Thus, we examined primary antibiotic resistance in clinical isolates of H. pylori in Lima, Peru.Materials and methods: H. pylori strains were isolated from gastric biopsies of patients with histologically proven H. pylori infection. Primary antibiotic resistance among isolates was examined using E-test strips. Isolates were examined for the presence of the cagA pathogenicity island and the vacA m1/m2 alleles via polymerase chain reaction.Results: Seventy-six isolates were recovered from gastric biopsies. Clinical isolates showed evidence of antibiotic resistance to 1 (27.6%, n=21/76), 2 (28.9%, n=22/76), or ≥3 antibiotics (40.8%). Of 76 isolates, eight (10.5%) were resistant to amoxicillin and clarithromycin, which are part of the standard triple therapy for H. pylori infection. No trends were seen between the presence of cagA, vacA m1, or vacA m2 and antibiotic resistance.Conclusion: The rate of antibiotic resistance among H. pylori isolates in Lima, Peru, is higher than expected and presents cause for concern. To develop more targeted eradication therapies for H. pylori in Peru, more research is needed to better characterize antibiotic resistance among a larger number of clinical isolates prospectively. Keywords: H. pylori, antibiotic resistance, Peru, amoxicillin